Biomechanical report for the IAAF World Championships London 2017 hammer throw men's - Dinsdale, A.; Thomas, A.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2018)
The men`s hammer final took place on the night of August 11th in good weather conditions. Coming into the final, Pawel Fajdeck of Poland was the favourite as the world leader in 2017. After the first two rounds, Aleksei Sokyrsii clinched an early lead with a season`s best throw of 77.50 m. Subsequently, Pawel Fajdeck then took control of the competition with an imposing sequence of throws, in which his best throw came in the fourth round which was measured at 79.81 m. Wojciech Nowicki was in the silver medal position going into the final round after throwing 78.03 m in the third round. In an enthralling finish, Valeriy Pronkin seized the silver medal with a throw of 78.16 m. However, Nowicki was unable to respond to this late surge from Pronkin which meant Nowicki had to settle for the bronze medal. (Attention! registration on the IAAF site is required for downloading)